Factors that contribute turnover intention among the employees of Seremban Specialist Hospital / Siti Aishah Ab Jalil - Ab Jalil, Siti Aishah (2009)
This research is conducted to carry out “Factors that contribute turnover intention among the employees of Seremban Specialist Hospital”. The main objective is to measures and identify the most factor that influencing employee’s intention to quit in an organization. It consist of four factor that are understanding job position/job description, organization management/ commitment and involvement from supervisor, individual feeling/ perception toward job and satisfied or dissatisfied toward working environment. This research were been used the probability sampling techniques and simple random techniques to get the data that are require. The research population is the employees at Seremban Specialist Hospital and the sampling frame for this research is the employee at Seremban Specialist Hospital, Seremban. About 118 respondent were getting from the research to help for accomplish this research by answering questionnaires had been distributed to them. All the data collected through the question were analyzed systematically by Statistical Package for Social Science (SPSS 16.0.1). The conclusion of this study was the outcome from the data analysis and findings. Through the research, it shows based on Frequency and Descriptive Statistic, a clear finding and results are observed. The finding showed the most factors that contribute to turnover are satisfied or dissatisfied toward working environment. Besides than that decision to quit among employees are moderate.